2009
DOI: 10.1002/micr.20632
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic nerve injection palsy in the child: Early microsurgical treatment and long‐term results

Abstract: Sciatic nerve injury caused by intramuscular injection in the gluteal region in the child seems as a sensory-motor palsy of the lower limb of variable degree. In preterm children or in children with severe perinatal distress, requiring intensive care, a drop foot is often missed or misdiagnosed as a malformative clubfoot or late diagnosed. Intramuscular drug injection (mainly antibiotics) during early infancy is another cause of injury. There are very few literature reports on postinjection trauma and on thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 10 publications
(5 reference statements)
0
30
0
4
Order By: Relevance
“…Naloxone with hydroxybenzoate, vitamin K with glycocholic acid and lecithin, and glycocholic acid and lecithin used alone were the least neurotoxic, but still caused nerve injuries. 20 Gentili et al 10 reported a moderate degree of nerve-fibre damage after intrafascicular injections of chloramphenicol, gentamicin, iron dextran and cephalothin in rats, with more damage being seen in large fibres. Extrafascicular injections did not always produce nerve damage.…”
Section: Agents Associated With Sniimentioning
confidence: 99%
See 3 more Smart Citations
“…Naloxone with hydroxybenzoate, vitamin K with glycocholic acid and lecithin, and glycocholic acid and lecithin used alone were the least neurotoxic, but still caused nerve injuries. 20 Gentili et al 10 reported a moderate degree of nerve-fibre damage after intrafascicular injections of chloramphenicol, gentamicin, iron dextran and cephalothin in rats, with more damage being seen in large fibres. Extrafascicular injections did not always produce nerve damage.…”
Section: Agents Associated With Sniimentioning
confidence: 99%
“…29 Ropivacaine administered intraneurally into the sciatic nerve of rats caused severe demyelination and Wallerian degeneration. 26 Senes et al 20 evaluated the neurotoxicity of several agents; hydroxybenzoate, alcohol and glycerol diacetate were found to be the most neurotoxic, with cefuroxime sodium and phenobarbital being moderately neurotoxic. Naloxone with hydroxybenzoate, vitamin K with glycocholic acid and lecithin, and glycocholic acid and lecithin used alone were the least neurotoxic, but still caused nerve injuries.…”
Section: Agents Associated With Sniimentioning
confidence: 99%
See 2 more Smart Citations
“…vasküler nedenler (7), gluteal bölgeye yapılan enjeksiyonlar (8) ve viral enfeksiyonlar sayılabilir (3). Kemik iliği aspirasyonu sonrası oluşan komplikasyonlar hemorajiye bağlı olup, bu durum en sık olarak miyeloproliferatif hastalık varlığında gerçekleşmektedir (5).…”
Section: Sayın Editörunclassified